ASSESSING ALEXITHYMIA: A PILOT STUDY USING A COMBINED DESIGN IN A SAMPLE OF LONG TERM DRUG USERS. (11th November 2018) - Ribeiro, O; Souto, T; Conde, R; Alves, H; Costa Pinto, L
Abstract: Among individuals with the diagnosis of substance-related and addictive disorders (DSM5) the presence of alexithymia is a well-established fact. Out of a sample of 117 middle-aged and older adults (74% aged between 40 and 64) with long-term history of drug dependence who are currently undergoing a treatment plan defined by national drug services, 55 (80% male; Mage=45.10, SD=9.18) were found to have alexithymia as assessed by The Toronto Alexithymia Scale (TAS-20). TAS-20 is a self-report questionnaire that quantitatively measures three components of alexithymia: difficulty in identifying feelings in the self (DIF), difficulty describing feelings (DDF), and externally orientated thinking (EOT). However, in this sample, the expression of the EOT subscale was found to have a minor impact on the global score. This finding is corroborated by previous studies that support TAS-20's psychometric limitations. To overcome this, a qualitative methodology was introduced to obtain in depth information about the expression of alexithymia in this sub-sample. A semi-structured interview was developed to explore the expression of the subscales mentioned for alexithymia. The interviews were analysed using content analysis. The results underscore a superficial report of emotions and a tendency to describe the external context of the emotion rather than describing the emotional experience itself, which can be interpreted as part of EOT. These results suggest the usefulness of considering a complementary qualitative approach in the study of alexithymia. Clinical interviews that may explore and provide further information on the unique expressions of alexithymia are also be considered, namely for older age categories.